From intern to practitioner to academic: the role of reflection in the development of a 'sports scientist'. Issue 4 (4th July 2018) - Doncaster, Greg
ABSTRACT: Following my progression and development from an undergraduate sports science student to my present position as a lecturer in Coaching and Performance, I sought to reflect upon this journey and how each significant stage of my development has either challenged, developed, or influenced my career. In attempting to articulate and disseminate such information I have utilised reflective accounts that were recorded throughout this time. Consequently, the current paper seeks to present a reflective account of key stages within my own career and development, from the initial stages of a newly graduated sports science intern, into a novice practitioner undertaking a PhD before finally attaining a full-time position in academia. I hope that these insights into my own personal and professional development may help anyone seeking employment or working in the sports science industry.